Pembuatan Peta Sebaran Penyakit melalui Workshop Sistem Informasi Geografis - Muhammad Syukri; Rd. Halim; Rizalia Wardiah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The problem that often arises and is commonly found in the implementation of health planning at the health office is that the health planning system is still less effective in covering the needs and problems related to the health of the local community. The purpose of this Community Service (PKM) activity is to increase knowledge and skills in making disease distribution maps using the Quantum GIS application as one of the tools for making health plans. The training method is carried out by simulation and direct practice. The participants of this training were as many as 16 staff of Disease Control and Eradication the Jambi Provincial Health Office (P2P). Evaluation of activities using a pre-posttest questionnaire. The knowledge of P2P officers before training was dominantly lacking (43.8%) and after training the knowledge became dominantly good (75%). The results of this activity were obtained by increasing the knowledge and skills of P2P officers in making disease distribution maps using the QGIS application.